IMPROVEMENT OF HYDRAULIC PRESS FOR VEGETABLE OIL EXPRESSION IN RURAL AREAS - Kibazohi, Oscar; Damson, Leonard (Tanzania Journal of Engineering and Technology, 2017)
Cultivation of oil producing crops especially Jatropha and croton as source of vegetable oil for biodiesel production is being encouraged in rural areas. To recover oil from seed, manual press is the feasible method in rural areas where there is no electricity. Research was conducted to improve hydraulic oil press machine for rural application. Factors affecting oil recovery were found to be: moisture content of seeds, operating pressure, seed oil content, and the amount of seeds pressed per batch. Percentage oil recovery was improved by reducing diameter of press cylinder, hence increasing expression pressure, and either reducing amount of seed processed per batch or placing disk within the seeds to improve oil flow. The maximum vegetable oil recovered from Jatropha seeds at a pressure of 20.8 MPa after improvement was 57.5% of the total oil in seeds. There was no significant difference in terms of oil recovery between pressing whole seeds or milled seeds. Suggested further improvement includes: higher pressure than 20.8 MPa, reduced radial distance travelled by oil and replacement of hydraulic jack with a self retracting double acting hydraulic power cylinder to reduce batch cycle.